PENINGKATKAN KEMAMPUAN GERAKAN SHOOTING PADA PERMAINAN BOLA BASKET MELALUI TEKNIK PERMAIN - muji hartono (Jurnal Lingkar Mutu Pendidikan, 2023)
The results of teaching and learning activities for Physical Education, Sports and Health at MTs Negeri 24 Jakarta in basketball games, namely shooting, still have not reached the KKM target. This is caused by several factors. First, the basic technique is wrong in shooting the basketball hoop. Second, the lack of students doing shooting movement exercises because they only rely on learning hours. The minimum completeness achievement has not affected the learning outcomes achieved by students. Therefore we need a method that can improve student learning outcomes in carrying out the ability to shoot to the basketball hoop, namely the game method. This research is Classroom Action Research (PTK) which aims to improve the results of Physical Education, Sports and Health lessons in the material is to do shooting movements. This research was conducted in two cycles with four meetings. Each meeting goes through four stages of activity, namely: planning, action, observation and reflection. This research was conducted in September-November 2018. The subjects of this research were students of class VIII.1 in the 2018/2019 academic year. Data collection techniques were carried out by tests, interviews, observations, and field notes. The research data is in the form of test results and observations of students' abilities in carrying out shooting movements in basketball games. The results of action research in cycle 1 meeting 1 the results of the shooting ability were 66 (66%) and in cycle I meeting 2 the results were 78 (78%). In cycle 2 meeting 1 the results of the shooting ability were 83 (83%) and in cycle II meeting 2 the results were 85 (85%). The attitude of students in the game showed an increase in the number starting from the first cycle of 86% to 92% of the second cycle. Thus, based on the results of the research data analysis, it can be concluded that the students' ability to perform shooting movements can be increased through basketball game techniques.